Initiating Hexagonal MoO3 for Superb-Stable and Fast NH4 + Storage Based on Hydrogen Bond Chemistry - Liang, Guojin (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.